Sosialisasi Pengolahan Limbah Plastik Menjadi Bahan Bakar Minyak Bagi Siswa-Siswi UPT SMA Negeri 4 Parepare - Nurmalasari, Nurmalasari; Putri, Syukrika; Bakri, Suriyanto; Prayitna, Yusri; Nisardi, Muhammad Rifki; Safitri, Dian; Rahmadani, Suci (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The increasing problem of plastic waste poses a serious environmental challenge and requires environmentally friendly and educational solutions. This community service activity aims to introduce the design and implementation of a plastic waste processing device that converts plastic into fuel oil (BBM) using the pyrolysis method, targeting students at UPT SMA Negeri 4 Parepare. The program was implemented through counseling sessions, interactive discussions, and demonstrations of the pyrolysis device, adjusted to the students’ level of understanding. Evaluation was conducted using pre- and post-tests, participant satisfaction surveys, and direct observation. The results showed that 84% of students demonstrated improved understanding of the material, and participation and satisfaction rates exceeded 90%. These findings indicate that the activity not only succeeded in raising students’ environmental awareness but also provided them with practical knowledge about simple technology for plastic waste management.